Efforts to Preserve the Balala’ Traditional Custom in the AGIL Perspective of Talcott Parsons in Lamoanak Village, Landak Regency - Gilang, Gilang; Ramadhan, Iwan; Wahyuni, Fauziah Sri; Imran, Imran; Utami, Patrisia Rahayu (Universitas Tanjungpura, 2025)
Indonesia is a country rich in diverse cultures and traditions, one of which can be found in West Kalimantan, known as the “Land of a Thousand Rivers.” In Landak Regency, the Dayak Kanayatn community continues to preserve their ancestral heritage through the Balala’ Traditional Ceremony, a one-day fasting or quiet period as an expression of respect to God (Jubata), nature, and their ancestors. However, modernization has led to a decline in the younger generation’s interest in maintaining this tradition. This study aims to analyze strategies for preserving the Balala’ Traditional Ceremony using Talcott Parsons’ AGIL theory, which includes the functions of Adaptation, Goal Attainment, Integration, and Latency (Pattern Maintenance). The research employs a descriptive qualitative method through observation, semi structured interviews, and documentation. The results show that the community has adapted the tradition to modern developments while maintaining its spiritual and social purposes, strengthening social integration through collective participation, and preserving cultural values through regeneration and the use of digital media.